1992
DOI: 10.1007/bf00028903
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial rps14 is a transcribed and edited pseudogene in Arabidopsis thaliana

Abstract: We have isolated and analysed a 2 kb region of the mitochondrial genome of Arabidopsis thaliana (Columbia) showing a high level of nucleotide identity with the mitochondrial (mt) rps14 small-subunit ribosomal protein gene from Oenothera berteriana and Vicia faba, as well as with an open reading frame (ORF) located upstream of the nad3 locus in O. berteriana. The rps14 locus is present as a single copy in the A. thaliana mt genome and has a translational stop codon located near the initiation codon, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…The nucleotide and deduced amino acid sequence comparison with those from other plant species showed that the rice rpl5 gene retains an intact ORF, whereas the original reading frame of the rps14 is interrupted by nucleotide deletions at four positions. A similar gene disruption has been reported in Arabidopsis (20,21) and potato (22), but the nucleotide deletion sites are different among the three plants. RNA gel blot analysis proved that the rps14 sequence was transcribed (see Fig.…”
Section: Rps14-related Sequence In Rice Mitochondrial Genome Issupporting
confidence: 71%
See 1 more Smart Citation
“…The nucleotide and deduced amino acid sequence comparison with those from other plant species showed that the rice rpl5 gene retains an intact ORF, whereas the original reading frame of the rps14 is interrupted by nucleotide deletions at four positions. A similar gene disruption has been reported in Arabidopsis (20,21) and potato (22), but the nucleotide deletion sites are different among the three plants. RNA gel blot analysis proved that the rps14 sequence was transcribed (see Fig.…”
Section: Rps14-related Sequence In Rice Mitochondrial Genome Issupporting
confidence: 71%
“…The presence of rps14 gene in the mitochondrial genome has been reported from lower plants such as liverwort (3) and chlorophyte alga (16). Among the higher plants, intact rps14 genes have been found in the mitochondrial genome of broadbean (17), Oenothera (18), and rapeseed (19), whereas rps14 is present as a pseudogene in Arabidopsis (20,21) and potato mitochondria (22). The nucleotide and deduced amino acid sequence comparison with those from other plant species showed that the rice rpl5 gene retains an intact ORF, whereas the original reading frame of the rps14 is interrupted by nucleotide deletions at four positions.…”
Section: Rps14-related Sequence In Rice Mitochondrial Genome Ismentioning
confidence: 99%
“…We believe this is unlikely because editing is known to occur in plant mitochondrial pseudogene transcripts that contain stop codons near the initiation codon (Schuster and Brennicke, 1991a;Aubert et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…3B, Table 3). This arrangement of the rpl5-pseudo-rps14-cob is conserved in both Arabidopsis and potato (Aubert et al 1992;Quiaeones et al 1996); other plants (such as Pisum sativum and Brassica napus) possess the rpl5-rps14-cob cluster with a functional rps14, and these genes are cotranscribed (Ye et al 1996;Hoffmann et al 1999). Regions of strong sequence similarities in the intergenic regions were evident in squash and watermelon, with a specific region of high similarity adjacent to cob present in all four cucurbits (Fig.…”
Section: Co-transcription Of Rrn5 and Rrn18 In Cucumbermentioning
confidence: 91%
“…The rpl5-rps14-cob and rrn5-rn18 operons are conserved in most plants (Aubert et al 1992;Ye et al 1993;Quiaeones et al 1996;Hoffmann et al 1999), including squash and watermelon, but are rearranged in Cucumis (Fig. 4B).…”
Section: Mitochondrial Genome Organization Within Cucumismentioning
confidence: 97%